2016
DOI: 10.13052/jmbmit2245-456x.413
|View full text |Cite
|
Sign up to set email alerts
|

Service and Data Driven Multi Business Model Platform in a World of Persuasive Technologies

Abstract: This article provides a new contribution to the concept of business models with the focus on the emerging gap between the usage of data, service and business models by suggesting a framework that function as a service and data driven business model platform. The purpose is to support manufacturing companies in establishing a service organization that delivers, creates and captures value through service and data driven business models by utilizing their network, resources and customers and/or users. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…In spite of the growth of data, many firms do not have strategies to use big data effectively [52,53], and thus are failing to benefit from integrating big data into their business models [54,55]. In response, a substantial number of studies have attempted to manage big data from the perspective of business model innovation, however, scholars have paid limited attention to the nature of the platform.…”
Section: Business Management Area For Data-driven Business Model Inno...mentioning
confidence: 99%
“…In spite of the growth of data, many firms do not have strategies to use big data effectively [52,53], and thus are failing to benefit from integrating big data into their business models [54,55]. In response, a substantial number of studies have attempted to manage big data from the perspective of business model innovation, however, scholars have paid limited attention to the nature of the platform.…”
Section: Business Management Area For Data-driven Business Model Inno...mentioning
confidence: 99%
“…In spite of the growth of data, along with the trends in digital business models and expected benefits from DDBMs, a recent global survey of~400 companies showed that 77 of companies do not have strategies to use big data effectively (Wang et al, 2015). Many companies are thus failing to benefit from integrating big data into their business models (Andersen & Bjerrum, 2016). The literature offers several reasons for such failures.…”
Section: Literature Review and Research Overviewmentioning
confidence: 99%